Manajemen Extracorporeal Membrane Oxygenation (ECMO) pada Pasien COVID-19 Derajat Kritis - Synthana, Meta Restu; Kurniawaty, Juni; Wisudarti, Calcarina Fitriani Retno (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2022)
We reported 42 years old male patient with weight 84 kg, height 167 cm, and BMI of 30.1 kg/m2 with a diagnosis of severe COVID-19 and ARDS. The patient was previously known to have comorbids of type 2 DM, stage 1 hypertension, cardiac arrhythmias, and grade 1 obesity. On the 7th day of care, the patient clinically and radiologically worsened and we decided to intubate and support with mechanical ventilation. An ECMO indication was assessed, the patient was indicated to have ECMO, so that ECMO was installed immediately after the patient was intubated. ECMO was successfully running 7 hours after the patient was intubated. During hospitalized the patient also received renal replacement therapy, hemadsorption therapy, and plasma exchange. The patient deceased on 31st day of ECMO.